Seasonal Variations of Chemical Weathering and CO2 Consumption Processes in the Headwater (Datong River Basin) of the Yellow River Draining the Tibetan Plateau - Yang, Liu; Zhang, Fei; Hu, Yadan; Zhan, Yun; Deng, Li; Huang, Huayu; Sun, Hui; Wei, Yaben; Li, Xiangliang (Frontiers in Earth Science, 2022)
The Yellow River basin covers contrasting tectonics, climate and vegetation settings. To explore the seasonal chemical weathering differences from the upstream to downstream of the Yellow River basin, we collected weekly river waters in the Datong River draining the Tibetan Plateau in 2017. Our results show remarkable seasonal variations of major ions. A forward model was employed to quantify the contribution of silicate, carbonate and sulfide oxidation and rain contributions to the cations, which yielded the contribution of 9.21±1.57%, 46.07±1.4%, 21.46±1.03% and 23.26±1.72%, respectively, indicating a dominated carbonate weathering to the river chemistry. The significant correlation between carbonate weathering rate and runoff suggests a critical runoff control on chemical weathering in the Datong River catchment. A comprehensive comparison between the upper and middle to lower reaches of the Yellow River basin shows a declined silicate weathering and CO2 consumption rate (ØCO2sil) from the upstream to downstream. In contrast, the physical erosion rate shows an increased trend, with the most prominent increase in the midstream loess Plateau. A further comparison between the Yellow River draining the Tibetan Plateau and the Loess Plateau shows 4.5 times higher ØCO2sil but 9.5 times lower erosion rate. In conclusion, we propose that runoff, rather than erosion, plays a central role on chemical weathering in the Yellow River basin, which provide insight for in-depth understanding the surficial weathering and the global carbon cycle.